Two-stage Heuristic for Primary School Timetabling Problem with Combined Classes Consideration - Sze, San Nah; Tan, See Yan; Chiew, Kang Leng; Tiong, Wei King (NSIGHT - Indonesian Society for Knowledge and Human Development, 2020)
This research focuses on a primary school timetabling problem, a small-scale primary school that is located at Pengerang, Johor. In this small-scale primary school, six classes have been allotted, from standard one until standard six. Most of the primary school timetables are manually developed, which is extremely time-consuming. According to the new policy announced on 12th Dec 2017by the Ministry of Education (MoE) Malaysia, due to the shortage of teachers, combined-classes should be implemented in lowenrolment schools with fewer than 30 students. MoE has introduced another policy on 30th June 2018 that recommends schools to reduce the number of subjects that are being taught in a day to solve the overloaded school bag issue. There is a set of hard constraints in this primary school timetabling problem due to the stipulation that a teacher can only teach one subject at a time; each subject must satisfy the total weekly period(s), and the combined classes can only combine one subject at a time. The main objective of this study is to propose a heuristic solution to this solves primary school timetabling problem with the consideration of combinedclasses. A two-stage timetabling heuristic approaches been offered due to its simplicity in dealing with numerous constraints. The twostage heuristic method was clustered into subject groups in the first stage to ease the timeslots allocation in the second stage. A clashfree timetable can be obtained from this proposed algorithm. The result generated by this proposed solution outperforms the current manual practice in solution quality and computing efficiency.